Experimental assessment of acoustic effects of cannon fire on crew - Stojadinović, Dragan R.; Jovanović, Snežana; Djurić, Aleksandar; Bukvić, Aleksandar; Perić, Sreten (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: The noise generated by artillery firing can have an extremely harmful effect on the people using it, namely the crew. The subject of this paper is the measurement and analysis of noise levels on artillery weapons used in the Serbian Army.Methods: The analysis and comparison of the results were carried out during operation of weapons of different calibers.  Also, the aspect of impact and risk on the crew exposed to the mentioned physical phenomena was considered.Results: The results of the examination of the acoustic parameters in relation to the available criteria show that the crew on certain vehicles is exposed to a higher level of noise than allowed.Conclusion: It is concluded that all measured noise levels exceed the prescribed limit value. Based on the obtained results, further work can be done on reducing negative physical phenomena, as well as providing adequate equipment for the protection of the crew.
Keywords: noise; measurement; assessment; risks; crew